The Influences of Migrant Settlement To The Local Community: An Analysis of Socio - Economic Aspect (Case of Ampenan and Sekarbela, Mataram Municipality) - Pratama, Reba Anindyajati (Magister Pembangunan Wilayah dan Kota,Undip, 2015)
Many cities in Indonesia are experiencing the high level of migration as the symptom urbanization process. In the other hand, the presence of the migrant in the urban area will bring changes to the local environment. As the case, Central Statistical Bureau reported Mataram has experienced 31% of recent migration in the province or recorded 36.326 new migrant during 2007-2012. Furthermore, Ampenan as one of the main sub district has been split into Sekarbela to accommodate the pressure of urban demand. This research aims to eradicate the existence of migrant and its influences in Ampenan and Sekarbela from socio-economic aspects. Specific objectives of the research are; eradicating the interaction between migrant and the place, and analyzing the influences of migrant settlement to the local community. This research finds there are different patterns on how lower and upper-middle migrant resided and contributed to the area of Ampenan and Sekarbela. The lower-middle migrant tend to have more influence to the informal sector and social relationship in the old town of Ampenan. The upper-middle migrant tend to have more influence in socio-economic transformation of the local people in Sekarbela due to the need of the new development.